Dėl asmeninių įvardžių formų (mūs)-uje ir (mūs)-yje kilmės - Rosinas, Albertas (Baltistica, 1971)
ON THE ORIGIN OF THE PERSONAL PRONOUNS (mūs)-uje AND (mūs)-yjeIn the article the author comes to the conclusion that the “plural” form of the personal pronoun (mūs)-uje in the Lithuanian dialect of East Prussia is as old as that of the adessive (mūs)-upi. The forms in question seem to derive from the non-paradigmatic locativ *(mūs)-u.The forms of the reflexive pronoun, having the complementary distribution of “plural” (but having no category of person), are, in some cases, substitutes for personal pronouns. This leads to the conclusion that the adessive (mūs)-upi could have been replaced by (mūs)-ipi, cf. savipi. Similar reasons may have caused the appearance of the inessive (mūs)-yje (cf. savyje); but its realization, at that time, became impossible as the contrast between the adessive and the inessive was neutralized. (In written records the adessive (mūs)-i(m)pi fulfils the function of the inessive).Only at the beginning of the 18th century when the necessity to unify the distinctive features of the inessive (i.e. to eliminate the contradiction between the identity and distinctive-features of the inessive) arose, was the adessive morpheme -i(m)p replaced by -yje which fitted best with the whole inessive system.